2014
DOI: 10.1002/rra.2785
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Impoundment on Macroinvertebrate Community Assemblages in Upland Streams

Abstract: Approximately 15% of the world's river flow is regulated, but evidence for the impacts of regulation on macroinvertebrate communities remains contradictory. Sound understanding of this topic is now required to meet legislative targets (e.g. EU Water Framework Directive good ecological potential). In the UK, research has either been undertaken at large (national) or small (reach) scales, and typically, researchers have made comparisons between sites classed simply as either regulated or unregulated. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…high torrentiality and seasonality) were dominated by EPT and OCH taxa whose traits provide resistance against disturbance, such as active aerial dispersal which favours dispersion and recolonization; (ii) in turn, reaches with more permanent and stable flow regimes, where higher primary production is expected, were characterized by detritivore species with a fully complete aquatic life-cycle. Moreover, Hydrobiidae was significantly more abundant in impounded streams (P \ 0.001), in agreement with results reported by Gillespie et al (2014). The distribution of this family is limited by stenotherm conditions (Oscoz et al, 2011), a fact that is highly related to the homogenization of stream temperature caused by dams, as well as the distribution of suitable lentic environments with high organic matter content.…”
Section: Invertebrate Communities In the Ebro Catchment: A Wider Medisupporting
confidence: 90%
See 1 more Smart Citation
“…high torrentiality and seasonality) were dominated by EPT and OCH taxa whose traits provide resistance against disturbance, such as active aerial dispersal which favours dispersion and recolonization; (ii) in turn, reaches with more permanent and stable flow regimes, where higher primary production is expected, were characterized by detritivore species with a fully complete aquatic life-cycle. Moreover, Hydrobiidae was significantly more abundant in impounded streams (P \ 0.001), in agreement with results reported by Gillespie et al (2014). The distribution of this family is limited by stenotherm conditions (Oscoz et al, 2011), a fact that is highly related to the homogenization of stream temperature caused by dams, as well as the distribution of suitable lentic environments with high organic matter content.…”
Section: Invertebrate Communities In the Ebro Catchment: A Wider Medisupporting
confidence: 90%
“…However, reduction of habitat heterogeneity and disturbance promote the colonization of invasive species, such as the snail Potamopyrgus antipodarum (Gray, 1843; mean densities of 3000 ind. m -2 ) in the Siurana, which has been also associated with regulation in the UK (Gillespie et al, 2014).…”
Section: Changes In Invertebrate Communitiesmentioning
confidence: 98%
“…Several macroinvertebrate families were found to increase in relative abundance at regulated sites, with the number of the caseless caddisfly larvae family Hydropsychidae increasing most markedly at downstream sites, while two Ephemeroptera families (Baetidae and Heptageniidae) displayed significant reductions. These findings are broadly in keeping with results recorded in previous research (e.g., Gillespie et al, ). Although a number of traits responded significantly to flow regulation, biological traits associated with life histories and feeding strategies were prominently affected.…”
Section: Discussionmentioning
confidence: 99%
“…We found that biomonitoring indices reflecting ecological preferences for substrate composition, trophic status, and flow parameters differed significantly between non‐regulated and regulated systems. This is in contrast to the findings of Gillespie et al (), who reported that the LIFE score responded negatively to regulation but that PSI and ASPT scores were largely unaffected. Moreover, our study found that incorporating biomonitoring indices within a multivariate context alongside functional traits resulted in a slightly higher proportion of ecological variance being accounted for between regulated and non‐regulated systems.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of river regulation on macroinvertebrates has been the focus of many studies worldwide (Behrend et al, 2012;Gillespie et al, 2014). Macroinvertebrates play essential role in aquatic systems, especially due to recycling and, in reservoirs, as important link in every food chain.…”
Section: Introductionmentioning
confidence: 99%